Operational Impact in the Convergence Process on IPSAS for Government Entities in Colombia (2017)
In Colombia, the General Accounting Office of the Nation undertook the project of convergence towards International Public Sector Accounting Standards (IPSAS) in Government Entities from 2018 as part of a strategy to strengthen competitiveness, governance, business development and economic growth, with the application of these international standards that are already taking place around the world. Therefore, these public organizations are obliged to comply with the new regulations and must structure a project through which they can plan the process that allows them to meet the goal. At the same time, it is necessary to identify the operational impacts in all areas to avoid difficulties during implementation and in this way to seek alternatives for risk mitigation and allocation of the necessary resources to carry out the activities and make the fundamental decisions in this transition.